Kajian Yuridis Penerapan Pasal 378 KUHP pada Kasus Penipuan Jual Beli Proyek dan Jabatan di Lampung Selatan - Nabil El Rosyad; Firganefi Firganefi; Fristia Berdian Tamza (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Fraud in the buying and selling of projects and jobs is becoming more common and is causing unrest in society. The method used by the wrongdoers often involves making false promises and tricking others to gain personal benefits illegally. This study aims to look into how Article 378 of the Criminal Code applies to a fraud case in the buying and selling of projects and jobs in South Lampung, focusing on the Tanjung Karang District Court decision Number 467/PID.B/2023/PN TJK. The study uses a legal method that focuses on laws and specific case studies. Data were collected through literature reviews and examination of relevant court decisions. According to the discussion results, it is clear that the crime of fraud elements, as described in Article 378 of the Criminal Code, are present in this case. The accused was found to have committed deceit and told a series of lies that caused the victim to suffer financial losses. The court ruled that the accused was guilty and gave a sentence that matched the actions taken. The use of Article 378 of the Criminal Code in this case is seen as appropriate, providing protection for the victim and discouraging the offender. The conclusion of this study is that criminal law can effectively address fraud in the buying and selling of projects and jobs if there is strong evidence and proper legal procedures.